Land resources management system as basic constraint of socio-economical geography - Тишковець, Володимир; Опара, Володимир (Human Geography Journal, 2016)
The content of land resources management system as basic constraint of socio-economical geography has been shown. The detailed characteristic of socio-economical territorial groups as fundamental of land resources management system has been presented. The main principles, methods and directions of activity of land recourses state establishments management system of Ukraine, directed to land resources management mechanisms maintenance, regulation of questions of state and communal ownership management, providing of land ownership and land use registration system in the frames of state land cadastre.